Large Eccrine Acrospiroma of the Hand - Mahipathy, Surya Rao Rao Venkata (J Clin Diagn Res, 2017)
Eccrine acrospiroma are benign skin tumours of sweat duct origin. They usually present as small solid or cystic lesions which are confused clinically with other solid or cystic lesions. These are generally benign lesions with few reports of malignant transformation. Here, we report a case of a middle aged female presenting with a swelling of the dorsum of left first web space which was histopathologically diagnosed as an eccrine acrospiroma, which was managed with surgical excision and covered with a regional flap. This case is presented due to the large size of the lesion in the hand.